Non-homogeneous Fabry-Pérot antenna design process to improve aperture efficiency - Mateos-Ruiz, Pablo; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (My University, 2022)
A novel technique to design Fabry-Pérot antennas with non-homogeneous partially reflective surfaces (PRSs) is described. It uses a transmission line circuit model to efficiently obtain all necessary unit cell designs that satisfy the cavity resonance condition. This method allows an increase in directivity without reducing the bandwidth for a given footprint. Some design examples in the Ku-band are presented, showing the evolution from a simple single-layer PRS to a non-homogeneous two-layer one. The latter achieves an increase of about 3 dB in directivity while maintaining the bandwidth in electromagnetic simulations. This way, the gain-bandwidth product is improved from a value of 5 to almost 9, effectively raising the antenna efficiency.
Keywords: Antenas; Fabry-Perot, Interferómetros de; Ondas electromagnéticas de superficie; Sonido - Transmisión; Ingeniería acústica; Redes de banda ancha; Non-homogeneous; Partially Reflective Surface; 2D Leaky Wave Antenna; Circuit modelling; Wideband